CLIMATE CHANGE: IMPACT ON MYCOTOXINS INCIDENCE AND FOOD SAFETY - Dragan Milicevic; Brankica Lakicevic; Radivoj Petronijevic; Zoran Petrovic; Jelena Jovanovic; Srdjan Stefanovic; Sasa Jankovic (Теория и практика переработки мяса, 2019)
Climate change may have an impact on the occurrence of food safety hazards along the entire agri-food chain, from farm to fork. The interactions between environmental factors and food contamination, food safety and foodborne diseases are very complex, dynamic and difficult to predict. Extreme weather conditions such as floods and droughts which have not occurred previously in Serbia, may be supporting factors to contamination of crops by various species of toxigenic fungi and related mycotoxins. Mycotoxins are a group of naturally occurring toxic chemical substances, produced mainly by microscopic filamentous fungal species that commonly grow on a number of crops and that cause adverse health effects when consumed by humans and animals. Recent drought and then flooding confirmed that Serbia is one of the few European countries with very high risk exposure to natural hazards, as well as that mycotoxins are one of the foodborne hazards most susceptible to climate change.